Guía de laboratorio virtual para el aprendizaje de la hidrostática dirigido a estudiantes de la Unidad Educativa Chambo - Musuña Cushpa, Marlon Ivan (2024)
The present research aims to develop a virtual laboratory guide for learning hydrostatics. This study follows a quantitative methodology with a non-experimental, descriptive propositional design. The study subjects were students of the Chambo Educational Unit, involving a thorough analysis of learning needs in hydrostatics. Surveys and questionnaires were used as data collection instruments, revealing a predominance of traditional teaching methodologies and a strong interest in integrating more technologies into hydrostatics teaching. This interest stems from the perceived lack of interactive elements that could engage students and facilitate a more profound understanding. In conclusion, the educational context at the Chambo Educational Unit reveals a gap between employed teaching methodologies and modern pedagogical trends. Hence, the virtual laboratory guide for learning hydrostatics is proposed to enhance practical understanding of physical principles."